Implementasi Iptables Firewall dan Intrusion Detection System Untuk Mencegah Serangan DDoS Pada Linux Server - Widianto, Theodorus Kristian; Sulistyo, Wiwin (MEANS (Media Informasi Analisa dan Sistem), 2021)
Security on computer networks is currently a matter that must be considered especially for internet users because many risks must be borne if this is negligent of attention. Data theft, system destruction, and so on are threats to users, especially on the server-side. DDoS is a method of attack that is quite popular and is often used to bring down servers. This method runs by consuming resources on the server computer so that it can no longer serve requests from the user side. With this problem, security is needed to prevent the DDoS attack, one of which is using iptables that has been provided by Linux. Implementing iptables can prevent or stop external DDoS attacks aimed at the server.